Comparing Isometric Strengths of Shoulder Girdle Muscles in Females With and Without Scapular Dyskinesis - Afsun Nodehi Moghadam; Seyedeh Parinaz Vahabi; Ali Asghar Norasteh; Hamid Abolhasani (University of Social Welfare and Rehabilitation Sciences, 2018)
Objective Alteration of scapular position and motion is called scapular dyskinesis. Scapular dyskinesis is a common clinical problem. Strength of shoulder girdle muscles is important in shoulder motions and stability, so their weakness may lead to scapular dyskinesis. The aim of this study was to compare the maximum voluntary isometric force of shoulder girdle movements in subjects with and without scapular dyskinesis Materials & Methods A case-control study was designed where the participants were selected by nonprobability sampling; 30 subjects with scapular dyskinesis and an average age of 22.95±2.62 years and 30 subjects without scapular dyskinesis and an average age of 22.43±2.50 years. The subjects were instructed to stand with their arms resting on each side of the body. The examiner stood behind them at a distance of 1.5 meter and asked them to elevate their arms to the highest level possible. Scapular dyskinesis test was used to visually examine alteration in scapulohumeral rhythm during arm elevation in sagittal and frontal planes. The shoulder flexion and abduction were repeated for 5 times. At the same time, the examiner rated the scapular movement as normal or observable dyskinesis. The maximal voluntary isometric force of shoulder internal and external rotation on both sides, such as "scaption with external rotation", "scapular abduction and upward rotation", "scapular adduction and downward rotation", "scapular adduction" and "adduction and depression of scapula" were measured with manual Dynamometer. For determining the maximal shoulder isometric rotational force, subjects were positioned prone on tables, arm brought into 90º abduction in frontal plane with 90° elbow flexion and resistance given to distal forearm into shoulder external and internal rotations. The maximal isometric force of scaption (supraspinatus strength) was measured in seated position; shoulder elevated 70º into scapular plane abduction (scaption) with external rotation. The maximal isometric force of scapular abduction and upward rotation was determined in supine position while the arm was elevated to 90º flexion with elbow extension and resistance given against forward pushing. For determining the maximal isometric force of rhomboids and middle trapezius muscles, resistance was given against scapular adduction and downward rotation, and scapular adduction, respectively. The maximal isometric force of lower trapezius was determined in prone position while the arm was elevated to 135º shoulder elevation with elbow extension. Independent t-test was performed to compare the maximal voluntary isometric force of shoulder girdle motions in individuals with and without scapular dyskinesis. Results The mean±SD of age, weight and height of the participants without and with scapular dyskinesis were 22.43±2.50 years/ 22.95±2.62 years, 64.39±13.38 kg/ 65.67(±12.2) kg and 171.35(±11.29) cm/ 173.43(±8.66) cm, respectively. No statistically significant differences were found between the participants of the two groups with regard to the age, weight and height. Our result showed that the isometric force of "scaption with external rotation", "scapular abduction and external rotation", "adduction and depression of scapula", "scapular adduction and downward rotation" and "scapular adduction" were significantly different between the two groups (P<0.05). In comparison to the control group, the individual with scapular dyskinesis had weaker supraspinatus, serratus anterior, rhomboids and middle and lower trapezius muscles. Conclusion Scapular dyskinesia or altered kinematics of the scapula (downward rotation, anterior tilt and internal rotation) contributes to impingement syndrome by decreasing the subacromial space. The tissues that occupy the subacromial space are the supraspinatus tendon, subacromial bursa and long head of the biceps brachii tendon. The supraspinatus is the major rotator cuff muscle that is susceptible to tendinopathy in subacromial space. The inflammatory processes or tension overload during shoulder activities, which may result from altered kinematics of the scapula and decrease in the subacromial space, may lead to supraspinatus weakness. It has been shown that scapular stabilizers, such as serratus anterior, rhomboids and middle and lower trapezius muscles are more prone to weakness than the other shoulder muscles. So, the weakness in these muscles may relate to scapular dyskinesis. Scapular muscle exercises are executed in the rehabilitation of patients with subacromial impingement syndrome and scapular dyskinesis, as the muscular system is one of the major contributors to scapular positioning, both at rest and during movements. It seems that improving the strength of shoulder girdle muscles especially supraspinatus, serratus anterior, rhomboids, and middle and lower trapezius muscles would be necessary in individual with scapular dyskinesis.